Ativos intangíveis nas cooperativas agropecuárias: apontamentos teóricos e práticas atuais. - Souza, Aida Maria de (Universidade Federal do Tocantins, 2023)
This study seeks to know what the current practices of disclosure of intangible assets in societies Brazilian agricultural cooperatives. Through literature review and document analysis, we defined what are intangible assets and what the criteria for identifying them. Studies of Kayo (2002), among others have helped define the taxonomy of intangible assets. To identify the current practice of disclosure of intangible assets, sought to know the amount of Brazilian agricultural cooperatives, which had websites, how many publish economic and financial information and which showed intangible assets in the set of financial statements or management report. The data collected are the years 2013, 2014 and 2015, considering this last year those statements already published. The baseline survey were the websites of OCB, SESCOOP and OCE. The results show that there are few agricultural cooperatives that show information of intangible assets; that a significant number of agricultural cooperatives does not have a website, so the economic-financial information is not accessible on the world wide web. The main recommendation that is made is that cooperatives representations must devise ways to promote the inclusion of Brazilian agricultural cooperatives on the World Wide Web and is today one of the most used tools to access information. This will strengthen the segment of agricultural cooperatives and help promote cooperative principles, such as the democratic management. Particularly, the practice of information disclosure helps form leaders about the nature and benefits of cooperation.